2013
DOI: 10.3390/f4010106
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Whole-Tree Water Use Following Live-Crown Pruning in Young Plantation-Grown Eucalyptus pilularis and Eucalyptus cloeziana

Abstract: Pruning of live branches is a management option to enhance wood quality in plantation trees. It may also alter whole-tree water use, but little is known about the extent and duration of changes in transpiration. In this study, sap flow sensors were used to measure transpiration for 14 days prior to, and 75 days following the removal, through pruning, of the lower 50% of the live-crown length of 10-11 m tall four-year old Eucalyptus pilularis Sm. and E. cloeziana F. Muell. trees. Pruning had no effect on stem g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…For instance, Roberts, Vertessy, & Grayson (2001) reported that the mean daily tree transpiration of Eucalyptus sieberi aged 14, 45, and 160 years, were 10.6, 21.8, and 49.4 L day −1 , respectively. Another study (Alcorn et al, 2013) showed that the mean daily transpiration of the individual E . pilularis and E .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Roberts, Vertessy, & Grayson (2001) reported that the mean daily tree transpiration of Eucalyptus sieberi aged 14, 45, and 160 years, were 10.6, 21.8, and 49.4 L day −1 , respectively. Another study (Alcorn et al, 2013) showed that the mean daily transpiration of the individual E . pilularis and E .…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Roberts, Vertessy, & Grayson (2001) reported that the mean daily tree transpiration of Eucalyptus sieberi aged 14, 45, and 160 years, were 10.6, 21.8, and 49.4 L day −1 , respectively. Another study (Alcorn et al, 2013) showed that the mean daily transpiration of the individual E. pilularis and E. cloeziana trees (both tree species were 5-6 years old) ranged from 9 to 16 L day −1 . In our study, the whole tree transpiration for young, mature, and old trees during the whole experimental period was in the range of 3-15, 8-20, and 12-32 L day −1 , respectively.…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…For example, trees can compensate for a 25% or more defoliation treatment, showing no changes in concentration of nonstructural carbohydrates (Körner, 2003; Boege, 2005; Würth et al, 2005). A crown removal of 50% in Eucalyptus species showed no significant reduction in height and diameter increments over a 2-year period (Alcorn et al, 2008; Alcorn et al, 2013), indicating the great capability of trees to maintain above-ground growth rate from their reserve pools despite loss of foliage. On the contrary, Fraxinus stem growth responded to defoliation, by showing reduced growth rate initially, but recovering in the second year after the treatment, and remaining consistent in the following years ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it may be possible to reduce the nutrient consumption of the aerial part of Polygonatum cyrtonema by topping so that the underground rhizome can distribute more nutrients and promote its expansion. The wound-inducing effect after the topping causes the strong compensatory growth of Polygonatum cyrtonema 23,24 , thereby driving the accumulation of underground rhizome biomass.…”
Section: Effects Of Plant Topping On Rhizome Yield and Functional Com...mentioning
confidence: 99%